Analysis of Differences in Discipline of Male and Female Students at SMA Negeri 9 Padang - Chindy Prata Sari; Linda Fitria; Indra Wijaya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to determine the differences in discipline between male and female students at SMA Negeri 9 Padang. The forms of discipline that must be carried out by students are self-discipline, class discipline, school discipline and academic discipline. The type of research used in this research is quantitative. The research population was 405 people registered in the 2024/2025 academic year, with a sample of 206 people taken using proportional sampling. This research examines differences in student discipline. The instrument used for data collection in this research was a questionnaire prepared according to the Likert model. Data analysis was carried out using statistical programs on SPSS 29 and Microsoft Excel computers. Based on the results of the t-test, it is known that the significance value of 2-sided equal variances assumed is smaller than 0.05, namely 0.00 < 0.05. So, it can be concluded that there is no significant difference between the discipline of male and female students at SMA Negeri 9 Padang.